Drug routes in out-of-hospital cardiac arrest: A summary of current evidence. (December 2022) - Hooper, Amy; Nolan, Jerry P; Rees, Nigel; Walker, Alison; Perkins, Gavin D; Couper, Keith
Abstract: Recent evidence showing the clinical effectiveness of drug therapy in cardiac arrest has led to renewed interest in the optimal route for drug administration in adult out-of-hospital cardiac arrest. Current resuscitation guidelines support use of the intravenous route for intra-arrest drug delivery, with the intraosseous route reserved for patients in whom intravenous access cannot be established. We sought to evaluate current evidence on drug route for administration of cardiac arrest drugs, with a specific focus on the intravenous and intraosseous route. We identified relevant animal, manikin, and human studies through targeted searches of MEDLINE in June 2022. Across pre-hospital systems, there is wide variation in use of the intraosseous route. Early administration of cardiac arrest drugs is associated with improved patient outcomes. Challenges in obtaining intravenous access mean that the intraosseous access may facilitate earlier drug administration. However, time from administration to the central circulation is unclear with pharmacokinetic data limited mainly to animal studies. Observational studies comparing the effect of intravenous and intraosseous drug administration on patient outcomes are challenging to interpret because of resuscitation time bias and other confounders. To date, no randomised controlled trial has directly compared the effect on patient outcomes of intraosseous compared with intravenous drug administration in cardiac arrest. The International Liaison Committee on Resuscitation has described the urgent need for randomised controlled trials comparing the intravenous and intraosseous route in adult out-of-hospital cardiac arrest. Ongoing clinical trials will directly address this knowledge gap.